2017
DOI: 10.1016/j.jtho.2017.09.379
|View full text |Cite
|
Sign up to set email alerts
|

OA 09.06 A Phase Ib Trial of Savolitinib plus Gefitinib for Chinese Patients with EGFR-Mutant MET-Amplified Advanced NSCLC

Abstract: with targeted gene sequencing. Recurrent alterations were defined as an alteration occurring more than 2 times. Recurrent acquired mutations were expressed in Ba/F3 and EGFR mutant (T790M+/-) NSCLC cells. Mutation expressing Ba/F3 cell lines were assayed for IL-3 independence, and mutation expressing NSCLC cell were screened against combination targeted TKIs. Result: EGFR mutant NSCLC patients treated with first-line therapy had a median PFS of 14 months; and, of the patients with pre/post-TKI tumor molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The safety of savolitinib has also been explored in other phase I studies in combination with osimertinib and gefitinib. The monotherapy toxicity profile of savolitinib at active doses makes combinations with other targeted therapies, such as osimertinib, feasible and such combination regimens are currently being investigated with preliminary data demonstrating a potentially acceptable tolerability profile (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The safety of savolitinib has also been explored in other phase I studies in combination with osimertinib and gefitinib. The monotherapy toxicity profile of savolitinib at active doses makes combinations with other targeted therapies, such as osimertinib, feasible and such combination regimens are currently being investigated with preliminary data demonstrating a potentially acceptable tolerability profile (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Tepotinib plus gefitinib also showed significantly better progression-free survival (PFS) and OS than chemotherapy in patients with MET amplification (16.6 months vs. 4.2 months; 37.3 months vs. 17.9 months, respectively) [ 20 ]. Two phase Ib clinical trials revealed that a combination of savolitinib and osimertinib or gefitinib showed promising antitumor activity and tolerable toxicity in patients with acquired MET -amplified NSCLC [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 Recently, at the 2017 WCLC meeting, Yilong Wu reported another phase IB trial of savolitinib plus gefitinib for Chinese patients with EGFR-mutant MET-amplified advanced NSCLC and confirmed a partial response was reported in 11 patients (25%). 17 At present, the NCCN guideline is recommending the use of crizotinib in the treatment of patients with MET ex14skipping mutations. However, for MET amplification, the situation is relatively complex, and the best cutoff value for amplification needs to be further determined.…”
Section: Discussionmentioning
confidence: 99%